Functional outcome of proximal tibial fracture treated surgically using locking compression plate - Aseri, Mahendra K.; Singh, Vijaypal; Sharma, Pradeep Kr. (International Journal of Research in Orthopaedics, 2018)
Background: Tibial plateau fractures are common intra-articular fractures, representing 1.2% of all fractures. These fractures are common in two age groups: as higher-energy fractures in younger patients and lower-energy fractures in elderly patients secondary to osteopenia. In the younger population, these injuries are associated with an increased incidence of complications like nonunion, infection, restriction of motion, and post-traumatic arthritis. The study aimed for final outcome of proximal tibial fracture using locking compression plate by minimally invasive percutaneous plate osteosynthesis (MIPPO). Methods: 30 cases of proximal tibial fractures were treated by using locking compression plate and studied from December 2015 to November 2017 in Department of Orthopaedics, Dr. S.N. Medical College associated group of Hospitals, Jodhpur. Results: All the selected 30 cases were followed up for 6 months. The average time for union of fracture was 21 weeks ranging from 18-24 weeks. Full weight bearing was not allowed until 12 weeks or complete fracture union. Partial immobilization was kept for 6 weeks in long knee brace. An average flexion was achieved upto0-1140. We observed 4 cases of postoperative complications that included 2 infections, one knee stiffness and one varus deformity. Conclusions: Surgical management of proximal tibia fractures with only lateral plating by MIPPO gave excellent reduction, rigid fixation to restore articular congruity and provides early motion to achieve optimal knee function and reducing post-traumatic osteoarthritis.